2022
DOI: 10.3389/fmed.2022.751929
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Further Mismanagement of Fever During COVID-19 Pandemic: Possible Causes and Impacts

Abstract: Fever remains an integral part of acute infectious diseases management, especially for those without effective therapeutics, but the widespread myths about “fevers” and the presence of confusing guidelines from different agencies, which have heightened during the coronavirus disease 2019 (COVID-19) pandemic and are open to alternate interpretation, could deny whole populations the benefits of fever. Guidelines suggesting antipyresis for 37.8–39°C fever are concerning as 39°C boosts the protective heat-shock an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…not necessarily due to the supposed absence of correlation as proposed by Arlehamn et al 3 The apparent progressive closing of the gap in COVID-19 impact on differential TIC prevailing populations (<10 and >10% LTBI) would be also being contributed by interventions or measures undertaken, for example, the introduction of vaccines and development of a gradual increase in herd immunity, changing COVID-19 stringency measures (https://ourworldindata. org/grapher/covid-stringency-index accessed on March 28, 2022), 19 confusions regarding fever management that controls pertinent immune responses (cell-mediated and antiviral), 20,21 possible over prescription or self-medication of supposed immune augmenting agents like Vitamin D 13 and Zinc. 14,22,23 The East and the West Germany States that have been proposed in the early stage of the pandemic to be 9 , consistently reported lower i-CFR as compared to the West Germany States (estimated LTBI 9.2% LTBI.…”
Section: Resultsmentioning
confidence: 99%
“…not necessarily due to the supposed absence of correlation as proposed by Arlehamn et al 3 The apparent progressive closing of the gap in COVID-19 impact on differential TIC prevailing populations (<10 and >10% LTBI) would be also being contributed by interventions or measures undertaken, for example, the introduction of vaccines and development of a gradual increase in herd immunity, changing COVID-19 stringency measures (https://ourworldindata. org/grapher/covid-stringency-index accessed on March 28, 2022), 19 confusions regarding fever management that controls pertinent immune responses (cell-mediated and antiviral), 20,21 possible over prescription or self-medication of supposed immune augmenting agents like Vitamin D 13 and Zinc. 14,22,23 The East and the West Germany States that have been proposed in the early stage of the pandemic to be 9 , consistently reported lower i-CFR as compared to the West Germany States (estimated LTBI 9.2% LTBI.…”
Section: Resultsmentioning
confidence: 99%
“…[26,27]. It would be interesting to know how these mortality sex ratios among countries would have varied with various proposed explanatory and protective variables [28][29][30][31] including widely adopted inappropriate nutrient supplementations and medications [32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…In view of these problems of access to healthcare, authors such as Hogan et al (2020) and Weiss et al (2020) have quanti ed the additional loss of life that could be caused by other diseases [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Thus, using cases from low-and middle-income countries, Hogan et al (2020) showed that deaths from HIV, tuberculosis and malaria over 5 years could increase by up to 10%, 20% and 36%, respectively, compared with if there were no COVID-19 pandemic [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, fever is a symptom of other illnesses, such as malaria and dengue fever. Although fever is a defence mechanism in the event of infection, not always requiring treatment except in the event of aggravation [7], during the pandemic period, the WHO recommended that people in areas where malaria or dengue fever is rare should consult a professional immediately in the event of fever 1 . In fact, the aim is to detect whether the fever is a sign of COVID-19, requiring screening in order to isolate the sick person to prevent the disease spreading, or if it is a sign of another disease requiring treatment of the disease in question.…”
Section: Introductionmentioning
confidence: 99%